2019
DOI: 10.21608/eja.2019.18567.1007
|View full text |Cite
|
Sign up to set email alerts
|

Basil oil nanoemulsion formulation and its antimicrobial activity against fish pathogen and enhance disease resistance against Aeromonas hydrophila in cultured Nile tilapia

Abstract: Pure basil oil which has antimicrobial and immunostimulant effect in the cultured fish was formulated into nanoemulsion using homogenizer. Basil oil nanoemulsion characters, its effect as antimicrobial in vitro and its resistant against Aeromonas hydrophila were studied. The results revealed that the droplet size distribution of the basil oil nanoemulsion measured 6.419 nm in diameter with poly dispersity index (PDI) value 0.753, Zeta potential-1.01mV, pH value 5.55, the conductivity 203.5 µS/m and the viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Gulec, et al [101] [119]. It was determined that S. agalactiae had high susceptibility towards the O. Basilicum [105], M. piperita [45], C. Nardus [102], and S. Aromaticum [103] with MIC value of 9 µL/mL, 0.125 mg/mL, 0.244 µg/mL, and 0.015 µg/mL, respectively.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
See 3 more Smart Citations
“…Gulec, et al [101] [119]. It was determined that S. agalactiae had high susceptibility towards the O. Basilicum [105], M. piperita [45], C. Nardus [102], and S. Aromaticum [103] with MIC value of 9 µL/mL, 0.125 mg/mL, 0.244 µg/mL, and 0.015 µg/mL, respectively.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…A strong inhibitory effect of Ocimum basilicum EO with 3 μL/mL and 9 μL/mL MIC values was reported on A. hydrophila and A. veronii , respectively [ 105 ]. Among nine different herb EOs, Conobea scoparioides and Lippia origanoides EOs had remarkable activity against A. hydrophila with the low respective MIC and MBC values of 200 μg/mL [ 106 ].…”
Section: Essential Oils As Antibacterial Agents: An In Vitro Perspmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed beneficial effects of these bioactive compounds on growth, immunity, antibacterial and antiparasitic activities in fish crops [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In particular, Ocimum basilicum was effective against Streptococcus agalactiae and Pseudomonas fluorescens , pathogens of particular concern for farmed fish [ 19 ].…”
Section: Introductionmentioning
confidence: 99%